Local Subculture and Instagram Food Influencers: Effects on Consumer Attitudes, Engagement, and Purchase Preferences for Bogor Souvenirs - Ahmad Badari Burhan; Aprilianti Pratiwi; Sayyidah Afifah; Nadhira Anabilla Divanya (ULTIMA Comm, 2026)
This study investigates how local subcultures and Instagram food influencers shape consumers’ purchase preferences for Bogor’s local food and souvenir products, with consumer engagement and consumer attitudes serving as mediating mechanisms. Conceptually, the research brings together Consumer Culture Theory and the Theory of Planned Behavior and situates both within the digital media landscape of Instagram. Adopting a quantitative explanatory design, the study draws on survey responses from 208 Instagram users, which were analyzed using SEM-PLS. The results show that among all the constructs examined, consumer attitudes stand out as the most powerful predictor of purchase preference, underscoring how decisive favorable evaluations are in consumer decision-making. Engagement, although a comparatively weaker direct driver of purchase preference, proves to be an important mediator alongside attitudes. Notably, the strongest indirect pathway runs from local subculture through consumer attitudes to purchase preference, a result that foregrounds the central role of cultural identity. Taken together, the findings extend CCT by demonstrating that cultural values persist even within digital media settings, and they reinforce TPB by reaffirming attitude as a primary determinant of behavioral preference, rather than competing, drivers of consumer behavior.